2014
DOI: 10.1016/j.brat.2014.08.008
|View full text |Cite|
|
Sign up to set email alerts
|

The neuroscience of depression: Implications for assessment and intervention

Abstract: Major Depressive Disorder (MDD) is among the most prevalent of all psychiatric disorders and is the single most burdensome disease worldwide. In attempting to understand the profound deficits that characterize MDD across multiple domains of functioning, researchers have identified aberrations in brain structure and function in individuals diagnosed with this disorder. In this review we synthesize recent data from human neuroimaging studies in presenting an integrated neural network framework for understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 180 publications
0
34
0
2
Order By: Relevance
“…Studies show that depression evolves with a reduction in the size of the prefrontal cortex and the blood flow to that area (Porto et al, 2002;Singh and Gotlib, 2014). Possibly, these changes are associated with reduction of BDNF, since this factor is responsible for neurogenesis and neuroplasticity of the central nervous system (Kimpton, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Studies show that depression evolves with a reduction in the size of the prefrontal cortex and the blood flow to that area (Porto et al, 2002;Singh and Gotlib, 2014). Possibly, these changes are associated with reduction of BDNF, since this factor is responsible for neurogenesis and neuroplasticity of the central nervous system (Kimpton, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Given the convergence of structural and functional data implying cerebellar contributions to MDD symptoms, this hypothesis warrants further research. Discerning brain differences that reflect the clinical state of depression from neurobiological traits that predispone individuals to MDD is of utmost scientific and clinical interest (Singh and Gotlib 2014). To elucidate whether abnormal cerebellar strucuture constitutes a state-or a trait-like characteristic of MDD, we here included a group of remitted patients who had major depression but who were not currently depressed.…”
Section: Discussionmentioning
confidence: 99%
“…Neural changes resulting from the social defeat stress model include decreased arborization in the hippocampus -an area known to be important in both memory formation as well as in the stress response [18,19 ] -changes in brain derived neurotrophic factor (BDNF; decreases in the hippocampus and increases in the mesolimbic dopamine circuit), decreased CREB (cyclic-AMP-response-element-binding-protein) activity in the hippocampus, increased Hypothalamic Pituitary Adrenal-Axis (HPA) activity [16,17], and changes in interactions between striatal, amygdalar and medial frontal regions [20,21]. Changes in hippocampal structure in rodent models of depression are paralleled by consistent findings in human depressed patients of decreased hippocampal size and gray matter density [22]. Further, the number of depressive episodes in humans is negatively correlated with hippocampal size further implicating the hippocampus in depression course [23].…”
Section: Animal Models Of Depression Coursementioning
confidence: 81%
“…Several recent meta-analyses have been published [22,[48][49][50][51]. Similar to the resting studies, a majority of studies have found abnormalities in fronto-limbic circuitry.…”
Section: Task-based Studiesmentioning
confidence: 82%